Comparison of Clinical and Laboratory Criteria of Neonates Born to SARS-CoV-2 Infected Mothers in Second and Third Trimester of Pregnancy - Akram, Nabeeha Najatee; Sadoon, Shurooq Talib; Nori, Wassan (AlQalam Journal of Medical and Applied Sciences, 2022)
Aims. To verify clinical, laboratory, and outcomes of neonates born SARS-CoV-2 infected pregnant women in second and third trimesters and assess the relation of the timing of infection to neonatal outcomes. Methods. A cross-sectional study recruited 126 neonates admitted to the neonatal care unit (NCU) whose mothers had confirmed SARS-CoV-2 infection; divided into groups I (72/126) and II (54/126) based on second and third-trimester infection, respectively. Neonatal data were collected, including gender, gestational age at delivery, birth weight, indication, and number of days for admission to NCU; blood parameters, and biochemical and inflammatory markers. Results. A trend of prematurity and low birth weight was reported in group I. APGAR score and admission days to NCU were comparable. Sepsis was frequently reported among admitted neonates, irrespective of group. Group I showed non-significant elevated neutrophil count while C-reactive protein was insignificantly higher in group II. Group, I had a trend of 2.5 odds ratio OR for low birth weight, 1.75 OR for more prolonged admission, while group II had 3.14 odds for elevated C-reactive Protein II. Conclusion. Low birth weight and longer NCU admission were common among second-trimester newborns; however, a favorable neonatal outcome was reported irrespective of the timing of maternal infection. Cite this article: Akram NN, Sadoon ST, Nori W. Comparison of Clinical and Laboratory Criteria of Neonates Born to SARS-CoV-2 Infected Mothers in Second and Third Trimester of Pregnancy. Alq J Med App Sci. 2022;5(2):585-591. https://doi.org/10.5281/zenodo.7443443